Outsourcing and offshoring of business services: Challenges to theory, management and geography of innovation - Silvia Massini; Marcela Miozzo (The University of Manchester, Manchester Business School, 2010)
Drawing on an original survey, we discuss the trends and challenges posed by the outsourcing and offshoring of business services. We document and analyse the increasing offshoring of business services (administrative services, call centres, IT services, procurement and product development) from USA and Europe to less developed countries, the functions offshored, size of offshorers, destination, and delivery models and explore the role of ICTs and the development of both large global services suppliers and entrepreneurial ventures in developed and less developed countries. We derive implications regarding outsourcing decisions, globalisation of high value adding activities, such as product development and innovation, raising issues of evolving market structure and the emergence of technical clusters where companies develop expertise to provide, and compete for, activities and skills across a range of sectors.
Keywords: O14; O30; O32; 330; outsourcing; offshoring; knowledge intensive business services; innovation